2012
DOI: 10.1002/jmri.23938
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI for prostate cancer localization in correlation to whole‐mount histopathology

Abstract: Combining T2w, DCE, and DW imaging significantly improves prostate cancer localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 42 publications
1
120
0
1
Order By: Relevance
“…17), and it was slightly higher than the correlation between tumor volume on T2-weighted MRI and histopathologic tumor volume reported by Turkbey and colleagues (r ¼ 0.63; ref. 23).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…17), and it was slightly higher than the correlation between tumor volume on T2-weighted MRI and histopathologic tumor volume reported by Turkbey and colleagues (r ¼ 0.63; ref. 23).…”
Section: Discussionmentioning
confidence: 54%
“…Tumor volume measured on DWI correlates well with the histopathologic tumor volume (17,18). However, the relationship between ADC and prostate tumor volume and the potential synergy of these two parameters in evaluating prostate cancer aggressiveness have not been explicitly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, dynamic contrast-enhanced (DCE) MRI was not performed as it was not standard-of-care in our institution at the time of this study, although there is some evidence that it can help improve sensitivity over DWI alone. 27,42,43 However, most lesions were in the TZ and the recently updated PI-RADS guidelines suggest DCE-MRI has no role to play in assessment of the TZ in the presence of adequate DWI and T2-weighted imaging. 44 There is differing nomenclature between the radiological sector-maps for reporting MRI-tumour location and the Ginsburg uropathology system used for obtaining and reporting biopsies; this may account for some analysis errors, as correlation of the MRI location to biopsy sectors becomes more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…DCE takes advantage of the unique characteristics associated with the abnormal tumor vasculature to assess aggressiveness of the disease. The usefulness of DCE in detecting, localizing, and staging prostate cancer is well documented in literature [58,[86][87][88][89][90]. Additionally, several studies have reported promising findings on the utility of DCE parameters in discriminating prostate cancer based on aggressiveness of the disease [91,92].…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%